Quality and Sensory Profile of Synbiotic Yogurt Enriched with Strawberry Pulp - Suharto, El Latifa Sri; Juliyarsi, Indri; Melia, Sri; Ferawati; Kurnia, Yulianti Fitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This study aimed to evaluate the effect of adding strawberry pulp (Fragaria × ananassa) at different concentrations on the sensory attributes of synbiotic yogurt. Sensory parameters, including texture, aroma, taste, and color, were assessed using a hedonic test. The sensory data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney post hoc test. The probiotic cultures used in this study were Lactobacillus fermentum L23, Streptococcus thermophilus, and Pediococcus acidilactici BK01. The treatments consisted of varying levels of strawberry pulp added to the synbiotic yogurt: P0 (0%), P1 (5%), P2 (10%), P3 (15%), and P4 (20%). The results indicated that strawberry pulp addition had a significant effect (P < 0.05) on the sensory scores of texture, aroma, taste, and color. The best sensory acceptance was observed in treatment P1, corresponding to the addition of 5% strawberry pulp to the synbiotic yogurt.